2022
DOI: 10.3390/children9050621
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review on Current Diagnostic Imaging Tools for Dentomaxillofacial Abnormalities in Children

Abstract: The current review narrates the findings and discusses the available diagnostic tools for detecting structural abnormalities. The review discusses several diagnostic tools, such as magnetic resonance imaging, cone beam computed tomography, multi detector row CT and positron emission tomography. The vital findings and comparative analysis of different diagnostic tools are presented in this review. The present review also discusses the advent of newer technologies, such as the HyperionX9 scanner with less field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Studies have shown updates of current imaging tools for imaging dentomaxillofacial abnormalities in children [136] , [137] , to obtain fetal dental 3D (panoramic) images [138] , and to perform diagnosis of cleft lip and palate in preclinical models [139] . Moreover, high-frequency ultrasound has shown efficacy on scanning subgingival crown preparation and gingival thickness [57] , [140] .…”
Section: Appraisal Of Previous Review Articlesmentioning
confidence: 99%
“…Studies have shown updates of current imaging tools for imaging dentomaxillofacial abnormalities in children [136] , [137] , to obtain fetal dental 3D (panoramic) images [138] , and to perform diagnosis of cleft lip and palate in preclinical models [139] . Moreover, high-frequency ultrasound has shown efficacy on scanning subgingival crown preparation and gingival thickness [57] , [140] .…”
Section: Appraisal Of Previous Review Articlesmentioning
confidence: 99%